An epigenome-wide association study in whole blood of measures of adiposity among Ghanaians: the RODAM study - Meeks, Karlijn A.C.; Henneman, Peter; Venema, Andrea; Burr, Tom; Galbete, Cecilia; Danquah, Ina; Schulze, Matthias B.; Mockenhaupt, Frank P.; Owusu-Dabo, Ellis; Rotimi, Charles N.; Addo, Juliet; Smeeth, Liam; et al. (Clinical epigenetics, 2017)
Background Epigenome-wide association studies (EWAS) have identified DNA methylation loci involved in adiposity. However, EWAS on adiposity in sub-Saharan Africans are lacking despite the high burden of adiposity among African populations. We undertook an EWAS for anthropometric indices of adiposity among Ghanaians aiming to identify DNA methylation loci that are significantly associated. Methods The Illumina 450k DNA methylation array was used to profile DNA methylation in whole blood samples of 547 Ghanaians from the Research on Obesity and Diabetes among African Migrants (RODAM) study. Differentially methylated positions (DMPs) and differentially methylation regions (DMRs) were identified for BMI and obesity (BMI ≥ 30 kg/m 2 ), as well as for waist circumference (WC) and abdominal obesity (WC ≥ 102 cm in men, ≥88 cm in women). All analyses were adjusted for age, sex, blood cell distribution estimates, technical covariates, recruitment site and population stratification. We also did a replication study of previously reported EWAS loci for anthropometric indices in other populations. Results We identified 18 DMPs for BMI and 23 for WC. For obesity and abdominal obesity, we identified three and one DMP, respectively. Fourteen DMPs overlapped between BMI and WC. DMP cg00574958 annotated to gene CPT1A was the only DMP associated with all outcomes analysed, attributing to 6.1 and 5.6% of variance in obesity and abdominal obesity, respectively. DMP cg07839457 ( NLRC5 ) and cg20399616 ( BCAT1 ) were significantly associated with BMI, obesity and with WC and had not been reported by previous EWAS on adiposity. Conclusions This first EWAS for adiposity in Africans identified three epigenome-wide significant loci ( CPT1A , NLRC5 and BCAT1 ) for both general adiposity and abdominal adiposity. The findings are a first step in understanding the role of DNA methylation in adiposity among sub-Saharan Africans. Studies on other sub-Saharan African populations as well as translational studies are needed to determine the role of these DNA methylation variants in the high burden of adiposity among sub-Saharan Africans.